Numerical simulation on Bay of Bengal's response to cyclones using the Princeton ocean model - Yashvant Das; Uma Charan Mohanty; Indu Jain (Brazilian Journal of Oceanography)
ABSTRACT This study used the Princeton ocean model (POM) which includes second-order turbulent closure scheme to investigate the fluid dynamics of the Bay of Bengal (BoB) in the upper ocean's response to a cyclone. The model uses an orthogonal curvilinear grid and 26 sigma levels in conformity with realistic bottom topography. The model is forced with wind and heat plus salinity fluxes as surface forcing to simulate the BoB's response during a cyclone. In order to provide the realistic cyclonic vortex the model as input, the synthetic cyclonic vortex is generated and superimposed on the QSCAT/NCEP blended ocean wind fields. Analyses of results show significant sea surface temperature (SST) cooling on both sides of the storm track. This cooling could be attributed to the strong cyclonic winds, surface divergence and upwelling. However, less commonly observed features such as a leftward bias in SST cooling due to the relatively slower motion of TC and southward moving coastal boundary currents are also reported in this study. Model SST is compared with the observed Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) filled up SST for the evaluation of the model's performance. Moreover, not only sea surface cooling but subsurface warming due to intense downwelling and coastal jet parallel to the coast were also observed in the model's simulation. The mixed layer depth (MLD) variation is revealed by the model. MLD deepening due to the convergence of near surface flow at the periphery of the cyclone is observed; however, beneath the cyclone centre, in the direction of the track the upsloping of isotherms due to the surface divergence and upwelling causes the shoaling of the MLD. Modeled surface currents are compared with 5-day interval OSCAR (Ocean Surface Current Analyses - Real time) surface currents, which are not very coherent, though some of the important features like higher values of boundary layer currents are captured. However, strong near surface, asymmetrical responses such as divergent currents in the open oceanic region are reflected by the model but when the cyclone approaches the coast the current patterns do not show the right bias due to interaction with the coast.